More than just a label: The impact of the vegan label on product perception and consumption intentions across health consciousness levels A quantitative study in the food industry - Berrer,Britney Tyra; Bernier,Manon (2025)
Purpose: The study aims to examine whether health consciousness, as a cognitive heuristic, influences the impact of vegan labels, as external cues, on product attribute perceptions such as taste, health, and environmental friendliness, as well as on consumption intentions. As consumers face cognitive limitations when evaluating food products, this research aim to contribute to the understanding of how external cues, such as vegan labels, and internal heuristics, such as health consciousness, influence consumption decision-making and the effectiveness of vegan labelling strategies. Methodology: This study employed a quantitative research approach with a deductive design. To investigate the proposed relationships, a single-factor between-subjects experimental design was incorporated into an online survey. Hypotheses were tested using PLS-SEM. Empirical data: Data were collected from 253 participants via convenience sampling, using multiple channels, including email, social media platforms and online forums. Findings: Results found that the vegan label didn’t have a significant effect on consumption intention. Equally, consumers product perception of healthiness, taste or environmental friendliness did not significantly mediate the relationship between the presence of the vegan label and consumption intentions. Furthermore, health consciousness did not moderate the relationship between the presence of a vegan label and consumers product perception of healthiness, taste and environmental friendliness or consumption intention. However, in line with previous studies, this research found that perceived taste and healthiness significantly influence consumption intention. Theoretical contribution: This study extends the theoretical understanding of consumer decision-making by applying Cue Utilization Theory to an underexplored context: the vegan food industry. It offers insights into how extrinsic vegan label cues are interpreted when intrinsic cues are unavailable, challenging common assumptions about the effectiveness of labels in shaping consumer behaviour. This study further adds nuance to the S-O-R Model. Rather than assuming a uniform pathway from stimulus to response, the study suggests that internal heuristics like health consciousness shape perception (the "Organism" component), leading to different consumption intentions and consumer perceptions. Practical contribution: Vegan labelling alone has a limited impact on consumer perception and consumption intention. To effectively influence consumption intention, marketers should complement vegan labelling with additional cues like taste-focused messaging and health claims. These elements align more with consumers preferences for healthy and flavourful food. To reduce interpretation gaps between consumer expectations and vegan products actual attributes, targeted marketing based on health consciousness, clearer labelling standards and better consumer education is needed. Retailers also play a key role through strategic integration of vegan products. Together, these strategies can increase the attractiveness and accessibility of plant-based options.
Keywords: Consumption Intention; Vegan label; Consumer Perception; Perceived Taste; Perceived healthiness; Perceived environmental friendliness; Health consciousness; S–O–R model; Cue utilization theory; Heuristics